Speak My Language and I Will Remember Your Face Better: An ERP Study - Baus, Cristina; Bas, Jesús; Calabria, Marco; Costa, Albert (Frontiers in Psychology, 2017)
Here we investigated how the language in which a person addresses us, native or foreign, influences subsequent face recognition. In an old/new paradigm, we explored the behavioral and electrophysiological activity associated with face recognition memory. Participants were first presented with faces accompanied by voices speaking either in their native (NL) or foreign language (FL). Then, faces were presented in isolation and participants decided whether the face was presented before (old) or not (new). The results revealed that participants were more accurate at remembering faces previously paired with their native as opposed to their foreign language. At the ERP level, we obtained evidence that faces in the NL were differently encoded than those in the FL condition, potentially due to differences in processing demands. During recognition, the frontal old/new effect was present (with a difference in latency) regardless of the language with which a face was associated, while the parietal old/new effect appeared only for faces associated to the native language. These results suggest that the language of our social interactions has an impact on the memory processes underlying recognition of individuals.